Reactivity and structure of derivatives of 2-hydroxy-1,4-naphthoquinone (lawsone) - Lamoureux Lamontagne, Guy (2007)
The structures of two derivatives of 2-hydroxy-1,4-naphthoquinone (lawsone) are examined using the density functional theory (DFT) hybrid functional B3LYP. Using the optimized structure of lawsone acetate, the reactivity of acyl transfer is described. Also, the nucleophilicity of the conjugate base of lawsone is predicted using the conceptual descriptors related to softness within the DFT framework